Multifunctional organic-inorganic hybrids based on cellulose acetate and 3-glycidoxypropyltrimethoxysilane - Silva, Robson R. [UNESP]; Salvi, Denise T. B. [UNESP]; Santos, Moliria V. [UNESP]; Barud, Hernane S.; Marques, Lippy F.; Santagneli, Silvia H. [UNESP]; Tercjak, Agnieszka; Ribeiro, Sidney J. L. [UNESP] (Springer, 2017)
Organic-inorganic hybrid films have been prepared from cellulose acetate (CA) and 3-glycidoxypropyltrimethoxysilane (GPTMS). Flexible films were fashioned with high relative content of GPTMS (up to 70 wt%) and exhibited high transparency in the visible/near-infrared region. The atomic force microscopy images of hybrid films display the presence of nanometric globular-like domains with size dependent and number dependent of the content of GPTMS. X-ray diffraction (XRD) patterns showed decreasing crystallinity of CA hybrid counterpart with increasing amounts of GPTMS. Spectroscopy results (vibrational spectroscopy FTIR and Raman scattering, C-13 and Si-29 NMR spectra) suggest that epoxy groups mostly remain intact and significant amount of methoxysilane groups is available after addition of GPTMS in CA. From Si-29 NMR results, all compositions showed the presence of non-hydrolized GPTMS molecules or having mono-and disubstituted siloxane bonds. For highest relative content of GPTMS (i.e., 50 wt%), a considerably high amount of non-hydrolized (T-0) is observed. Moreover, the addition of GPTMS leads to an increase in the thermal stability as compared to pure CA. Luminescent films were obtained by incorporating luminescent [Eu(TTA)(3)(H2O)(2)] complex (TTA = thenoyltrifluoroacetonate) into the hybrid films. Spectroscopic parameters did not significantly change with the incorporation of luminescent complex, suggesting application in photonics. The D-5(0) states quantum efficiency was observed to be the same for the neat complex and the luminescent hybrid film, suggesting a weak interaction with the host.
Keywords: Organic-inorganic hybrids; Cellulose acetate; 3-Glycidoxypropyltrimethoxysilane; Europium; Photoluminescence